Prenatal and postnatal supplementation with lipid-based nutrient supplements reduces anemia and iron deficiency in 18-month-old Bangladeshi children: A cluster-randomized effectiveness trial - Matias, Susana L; Mridha, Malay K; Young, Rebecca T; Khan, Md Showkat A; Siddiqui, Zakia; Ullah, Md Barkat; Vosti, Stephen A; Dewey, Kathryn G (Oxford Academic, 2022)
This article was published in the The Journal of Nutrition [© 2018 American Society for Nutrition. All rights reserved.] and the definite version is available at : https://doi.org/10.1093/jn/nxy078 The Journal's website is at: https://academic.oup.com/jn/article/148/7/1167/5036744